The Current Case and Peculiarities of Legal Support For the Development of Non-State Medicine in Ukraine - Prasol , Vladyslav (Pressing Problems of Public Administration, 2019)
An integral attribute of any civilized country is a stable, effective, adequate legal base. Legislation is the most important instrument of governmental regulation by which the government requires the execution of its decisions from the subjects of social relations. According to Article 5 of the Law of Ukraine “Fundamentals of the legislation of Ukraine on health care”, public health is recognized as a general obligation of society and the state. Today in Ukraine, the most important priority of state policy is to preserve and strengthen the health of the nation, based not only on the formation of a healthy lifestyle, but also on the reform of the health sector as a whole. The healthcare system's transformation (which is taking place in our country today) concerns everyone. Its goal is to provide all Ukrainian citizens with equal access to quality medical services and to rebuild the health care system to put the patient in its center.It should be noted that the active functioning of private (non-state) medical establishments give the state additional opportunities and bene ts,  rst of all, with a signi cant reduction of expenditures from the state budget and an increase in investments in the sphere of public health protection. Next bene t is establishment of market relations in the system in as a whole, and the development of healthy competition among health care providers and patient care facilities and their  nances. Also the availability of a developed private sector of medical services can reduce the burden on the public health system, as it serves a part of citizens who are able to pay for their treatment independently. All this updates a comprehensive study of the current state of legal base for the development of non-state medicine in Ukraine. The analysis of the current state of legal base for the development of non-state medicine in Ukraine provides ground for arguing that the legislative framework in the  eld of health was mostly created at the time when private medicine was at the  rst stage of its developing. Current normative and legal acts do not hinder the activities of non-state medical institutions, but do not promote the development of private medicine in Ukraine. Today, non-state medical institutions can actually provide all types of medical care at the level of state and local health care institutions (there is exception for restrictions on the use of narcotic drugs, issuance of sick leave, etc.). Consequently, for the development of the private sector of health care, it is necessary to bring the legal documents regulating the activities of private institutions into compliance ( rst of all, it concerns the implementation of the norms of the Law of Ukraine “On Public-Private Partnership”).